(untitled) (Journal of the Sociology and Theory of Religion, 2021)
The work done by the interest groups has been deeply analyzed since the seminal works from Easton (1990). However, the role of non-Catholic religious communities in general, and more concretely the Muslim community, has not been widely explained. Here it is aimed to make a dialogue between the works of Peña-Ramos (2016) and Peña-Ramos, García-Hípola & Díaz-Montiel (2019) that describe two attempts of structuring the political interests of this community in Spain. To do this, the cases of the city of Granada and the PRUNE political party will be compared, to see if they have a similar evolution and influence.